UPAYA PENINGKATAN HASIL BELAJAR PADA MATA PELAJARAN SEJARAH DENGAN MODEL PEMBELAJARAN DISCOVERY LEARNING DI KELAS X TAB SMK NEGERI 2 PAYAKUMBUH - ENDANG KURNIASIH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve learning outcomes in history lessons with the discovery learning model in class X TAB SMKN 2 Payakumbuh. The research that will be conducted is classroom action research. The subjects of this class action research were students of class X TAB which consisted of 33 boys and 2 girls. This research was conducted in class X TAB SMK Negeri 2 Payakumbuh. The use of a scientific approach to the learning model of Discovery learning can result in student learning. This is evidenced by the increase in student learning outcomes. In Pre-cycle learning, 23 students (65.71%) completed and 12 students did not complete (34.29%). Cycle I the number of students who completed increased by 25 people (71.24%) and students who did not complete decreased to 10 people (28.76%). For the second cycle the number of students who completed continued to increase by 30 people (85.71%) and students who did not complete continued to decrease to 5 people (14.29%). ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar pada pelajaran sejarah dengan model pembelajran discovery learning di kelas X TAB SMKN 2 Payakumbuh. Penelitian yang akan dilakukan adalah penelitian tindakan kelas. Subjek penelitian tindakan kelas ini adalah peserta didik kelas X TAB yang terdiri dari 33 orang laki- laki dan 2 orang perempuan. Penelitian ini dilaksanakan di kelas X TAB SMK Negeri 2 Payakumbuh. Penggunaan pendekatan saintifik model pembelajaran Discovery learning dapat hasil belajar peserta didik. Hal ini dibuktikan peningkatan hasil belajar peserta didik. Pada pembelajaran Prasiklus jumlah peserta didik yang tuntas 23 orang (65,71 %) dan peserta didik tidak tuntas 12 orang (34,29%). Siklus I jumlah peserta didik yang tuntas meningkat 25 orang (71,24%) dan peserta didik tidak tuntas menurun menjadi 10 orang (28,76 %). Untuk siklus II jumlah peserta didik yang tuntas terus meningkat 30 orang (85,71%) dan peserta didik tidak tuntas terus menurun menjadi 5 orang (14,29%).